Thermal ageing study of ZnO nanofluid–cellulose insulation. Issue 4 (28th October 2020) - Ibrahim, Asmaa; Nasrat, Loai; Elnoby, Ahmed; Eldebeiky, Soliman
Abstract : Trends in the studies of mineral oil (MO)‐based nanofluids (NFs) show that most of the conducted works have focused only on the thermal and dielectric properties but few numbers on the ageing performance. In the present study, ZnO NF, in combination with cellulose insulation experienced accelerated thermal ageing at 120 °C for 20 days to study the ageing performance and it was compared with that of MO–cellulose insulation. The deterioration rate of cellulose was evaluated through tensile strength, breakdown voltage (BDV) and dielectric dissipation factor properties. Whereas oils deterioration was evaluated through BDV, interfacial tension, kinematic viscosity, acidity and colour. The results demonstrate that for cellulose aged in NF (NFIP), the tensile strength and BDV are 3 and 6.9% higher, respectively; than those aged in MO. For aged oils, NF exhibits higher values of the viscosity and acidity by 3 and 33.3%, respectively, than MO. The BDV of NF is superior to that of MO in the initial ageing period, after that; it shows a lesser reduction tendency with ageing. The most important observation from this study is that despite this increment of ageing indicators for NF, it could improve the anti‐ageing properties of cellulose insulation.